The effect of organic and inorganic fibres on the mechanical and thermal properties of aluminate activated geopolymers - Masi, G.; Rickard, W.; Bignozzi, M.; Van Riessen, Arie (Elsevier Ltd, 2015)
The addition of fibres to a brittle matrix is a well-known method to improve the flexural strength. However, the success of the reinforcements is dependent on the interaction between the fibre and the matrix. This paper presents the mechanical and microstructural properties of PVA and basalt fibre reinforced geopolymers. Moreover low density and thermal resistant materials used as insulating panels are known be susceptible to damage due to their poor flexural strength. As such the thermal and fire resistance properties of foamed geopolymers containing fibre reinforcement were also investigated. The results highlight that the presence of PVA fibres greatly increased the flexural strength and the toughness of the geopolymer composite, while the presence of basalt fibres improved the flexural behaviour of the composite after high temperature exposure.